The Influence Of Safety Leadership And Safety Knowledge On Safety Attitude And Safety Citizenship Behaviour : (Case Study: Indonesian Railway (Persero)) - Mila Hikmatul Ulawia; Adithya Sudiarno (Yayasan Inovasi Kemajuan Intelektual, 2025)
Railways are a esential mode of transportation that face high safety risks, particularly in daily operational and maintenance activities. The high incidence of workplace accidents in this sector is often attributed to low levels of safety behavior among workers. This study aims to analyze the influence of safety leadership and safety knowledge on safety attitude and safety citizenship behavior (SCB) within the work environment of PT KAI (Persero). It also explores the role of work engagement and risk perception as antecedents of safety leadership and safety knowledge. A total of 60 permanent employees participated in the study, and data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results show that work engagement has a significant influence on safety leadership, while risk perception significantly affects safety knowledge. Both safety leadership and safety knowledge significantly enhance safety attitude. Furthermore, safety knowledge and safety attitude have a significant impact on SCB. However, the direct effect of safety leadership on SCB is not significant and is fully mediated by safety attitude. Theoretically, these findings emphasize the critical role of safety attitude as a mediator in promoting voluntary safety behavior. Practically, management should enhance employee engagement by establishing active safety representatives in each work unit to foster a participatory and sustainable safety culture.